The Role of the HST District Attorney's Office in the Coordination Team for the Supervision of Religious Beliefs and Cults in the Community - Mahya Rafiqa; H.Bahran, MH; Ilham Masykuri Hamdie (Sharia Journal and Education Center Publishing, 2023)
Abstract The implementation of freedom of religion and belief in Indonesia faces obstacles when it does not comply with government regulations. A research was conducted to examine the legal framework and institutions responsible for supervising religious beliefs and sects. The research used empirical methods including interviews, documentation, and observation. Primary data was collected on the supervision of belief flows in public order and tranquility, as well as the supervision carried out by the HST State Attorney's Office against misleading belief flows in the Hulu Sungai Tengah Regency. Secondary data included books, journals, articles, and research findings. The research found that the mechanism for supervising deviant religious sects and cults was not explicitly explained in the regulations, but interviews with sources revealed that the HST State Attorney's Office had its own mechanism involving decision letters, coordination meetings, and effective supervision. The supervision by the HST State Attorney's Office against cults in the district was deemed successful, resulting in legally binding decisions. Keywords: Religious, beliefs, cults, community Abstrak Pelaksanaan kebebasan beragama dan berkeyakinan di Indonesia menghadapi hambatan ketika tidak sesuai dengan peraturan pemerintah. Sebuah penelitian dilakukan untuk mengkaji kerangka hukum dan institusi yang bertanggung jawab untuk mengawasi keyakinan dan aliran keagamaan. Penelitian ini menggunakan metode empiris termasuk wawancara, dokumentasi, dan observasi. Data primer dikumpulkan mengenai pengawasan aliran kepercayaan terhadap ketertiban dan ketentraman masyarakat, serta pengawasan yang dilakukan oleh Kejaksaan Negeri HST terhadap aliran kepercayaan yang menyesatkan di Kabupaten Hulu Sungai Tengah. Data sekunder yang digunakan adalah buku, jurnal, artikel, dan hasil penelitian. Penelitian ini menemukan bahwa mekanisme pengawasan terhadap aliran kepercayaan dan aliran sesat tidak dijelaskan secara eksplisit dalam peraturan perundang-undangan, namun dari hasil wawancara dengan narasumber, Kejaksaan Negeri HST memiliki mekanisme tersendiri yang meliputi surat keputusan, rapat koordinasi, dan pengawasan yang efektif. Pengawasan yang dilakukan oleh Kejaksaan Negeri HST terhadap aliran sesat di kabupaten tersebut dinilai berhasil dan menghasilkan keputusan yang berkekuatan hukum tetap. Kata kunci: Agama, kepercayaan, aliran kepercayaan, masyarakat.